Appellate Procedures And Dispute Settlement Mechanism For Indonesian Trade Disputes - Isretno Israhadi, Evita (Opción, 1970)
This study aims at explaining and understanding the functions of a dispute settlement mechanism along with appellate procedures as evident from these select cases via comparative qualitative research methods. As a result, Indonesia proves weaker in cases against the western powers that have an influence in the World Trade Organization’s Dispute Settlement Body and also resources to manipulate its rulings. In conclusion, the WTO in general and DSB, in particular, have acted as a custodian of trade rights in most of the developing countries like Indonesia.